2ax=10a-3ax

Simple and best practice solution for 2ax=10a-3ax equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2ax=10a-3ax equation:


Simplifying
2ax = 10a + -3ax

Solving
2ax = 10a + -3ax

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-10a' to each side of the equation.
-10a + 2ax = 10a + -10a + -3ax

Combine like terms: 10a + -10a = 0
-10a + 2ax = 0 + -3ax
-10a + 2ax = -3ax

Add '3ax' to each side of the equation.
-10a + 2ax + 3ax = -3ax + 3ax

Combine like terms: 2ax + 3ax = 5ax
-10a + 5ax = -3ax + 3ax

Combine like terms: -3ax + 3ax = 0
-10a + 5ax = 0

Factor out the Greatest Common Factor (GCF), '5a'.
5a(-2 + x) = 0

Ignore the factor 5.

Subproblem 1

Set the factor 'a' equal to zero and attempt to solve: Simplifying a = 0 Solving a = 0 Move all terms containing a to the left, all other terms to the right. Simplifying a = 0

Subproblem 2

Set the factor '(-2 + x)' equal to zero and attempt to solve: Simplifying -2 + x = 0 Solving -2 + x = 0 Move all terms containing a to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + x = 0 + 2 x = 0 + 2 Combine like terms: 0 + 2 = 2 x = 2 Add '-1x' to each side of the equation. x + -1x = 2 + -1x Combine like terms: x + -1x = 0 0 = 2 + -1x Simplifying 0 = 2 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Solution

a = {0}

See similar equations:

| 8y+8=7y-12 | | 4t-2=33-3y | | 7m+38=5m-16 | | 3y=9-4x | | 3c+17=8 | | 3x-8x-5=-15 | | 5x-17=3x+4 | | 4q+3=-9 | | p-4+-9=p | | 2x(x+3)-7=5(5-x)+7(x+1) | | -5c(4c^2-2c)= | | 8x+(x*x)(x*x)=11 | | ln(16lnx)=2 | | 7+4q=11+3q | | 10x^2+15xy= | | 3(2x-4)=5x+9 | | x+2y+3z=13 | | 3x+29=2 | | 4x+4=-4+2x+12 | | 2abc=d | | 6a+18=30 | | 2x-1=2+2sqrt(x-4)+(x-4) | | 3x+6-8x-9= | | -5(-1)=8+4m | | 3x+2(x-1)=4x+4 | | 9x^2-18x+12=0 | | 8x-3+8x-3=10x+30 | | x=3.14*6*6*x | | (-5ab^2)(-6c^2)= | | 5m-3=-2m+4 | | 3x-7=-4x+14 | | 13=3.14d |

Equations solver categories